2010
DOI: 10.1021/ef100103z
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Diesel and Biodiesel Emissions Using Dimethyl Carbonate as an Oxygenated Additive

Abstract: Diesel vehicles account for the majority of new vehicles sales in Europe. This is due to inherent fuel efficiency and high reliability. Global warming concerns have seen demand for renewable alternatives to fossil diesel with low carbon dioxide (CO 2 ) producing emissions. Oxygenated biodiesel fuels such as rapeseed methyl ester (RME) can be utilized in an unmodified conventional diesel engine. RME combustion produces low emissions of unburnt total hydrocarbons (THCs), carbon monoxide (CO), and particulate mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(75 citation statements)
references
References 34 publications
5
69
0
1
Order By: Relevance
“…Dimethyl carbonate (DMC, CH 3 OCOOCH 3 ), a carbonate ester, is an attractive oxygenate compound for using as diesel fuel component for reducing soot emissions due to its good characteristics, such as: (1) 100% miscibility in diesel; (2) 53 wt% in oxygen content; (3) no carbon-carbon atomic bonds; and (4) relatively high H/C ratio [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Dimethyl carbonate (DMC, CH 3 OCOOCH 3 ), a carbonate ester, is an attractive oxygenate compound for using as diesel fuel component for reducing soot emissions due to its good characteristics, such as: (1) 100% miscibility in diesel; (2) 53 wt% in oxygen content; (3) no carbon-carbon atomic bonds; and (4) relatively high H/C ratio [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The oxygenates were chosen based on their cetane number and inherent oxygen content. While the former affects ignition delay, combustion duration and eventually NOx emissions [15], the latter influences smoke emissions [9]. Thus three oxygenates with a good range of oxygen content and cetane number, namely DMC, DGM and DEE, were chosen as three levels for the 'oxygenate-type' parameter.…”
Section: Selection Of Parameters and Its Levelsmentioning
confidence: 99%
“…Earlier researches have preferred blend proportions of oxygenates varying from 5 to 20 % in diesel [9,10,[14][15][16]. Blend proportions greater than 20 % have been reported to cause engine instability, fluctuations in engine speed and losses in power output [11] [15] [27].…”
Section: Selection Of Parameters and Its Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The effect of adding fuel-borne oxygen in the form of dimethyl carbonate (DMC) has been reported in (a non-toxic potentially bioderived 53.3% wt oxygenated additive) conventional pump diesel. 4 It was found that nitrogen oxides (NOx) increased and that THCs, CO, and PM were reduced by up to 50% with a 96% diesel, 4% DMC blend. Interestingly 2% DMC in diesel can generate comparable particulate, THCs and CO emissions to RME combustion, at just 1.1% wt oxygen.…”
Section: Introductionmentioning
confidence: 99%